EDUKASI TERKAIT KARTU MENUJU SEHAT (KMS) BALITA DAN MAKANAN PENDAMPING ASI (MP-ASI) DARI PROTEIN HEWANI - Wijinindyah, Ayutha; L. Lumban Gaol, Susan; Burhani Marda, Alexander (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
The high stunting rate in Central Kalimantan (26,9%) needs to be improved in several aspects, especially education for mothers of toddlers. The reality that occurs in society is thath there is still a lack of knowledge about the Card for Health (KMS) and Complementary Food for Breast Milk (MP-ASI) from local food ingredients among mothers of toddlers. The aim of this community service is to educate mothers of toddlers regarding KMS and MPASI from animal food. The method used was presentation of material and questions and answers to respondents. The result showed that many mothers of toodlers do not understand KMS. Giving MPASI to toddlers also uses minimal sources of animal protein. In the future, a deeper role for cardres is needed to educate KMS and MP-ASI for mother of toddlers